Induction of multiple signaling loops by MuSK during neuromuscular synapse formation - Moore, Chris (The National Academy of Sciences, 2001)
At the neuromuscular junction, two motor neuron-derived signals have been implicated in the regulation of synaptogenesis. Neuregulin-1 is thought to induce transcription of acetylcholine receptor (AChR) genes in subsynaptic muscle nuclei by activating ErbB receptors. Neural agrin aggregates AChRs by activating the receptor tyrosine kinase MuSK. Here, we show that these two signals act sequentially. Agrin, by activating MuSK, induces the synthesis and aggregation of both MuSK and ErbB receptors. ErbB acts downstream of MuSK in synapse formation. In this way, MuSK activation leads to the establishment of a neuregulin-1-dependent signaling complex that maintains MuSK, ErbB, and AChR expression at the synapse of electrically active muscle fibers.